The Significance of Public Consultation in the Design Process: The role of Public Participation in the Education of Architects - the Case Study of Development of Adam Mickiewicz Square in Opole - Kleszcz, Justyna; Wilczek, Iwona; Wilk, Kamila; Adamska, Monika Ewa (Civil and environmental engineering reports, 2025)
This article explores the significance of public consultation in the design process and its impact on architectural education, using the conceptual redevelopment of Mickiewicz Square in Opole as a case study. Public participation plays a crucial role in contemporary public space design, enabling the inclusion of residents' voices in decision-making processes. The first part of the article establishes the theoretical foundation of public participation, highlighting its influence on the quality and efficiency of design outcomes. This is followed by an in-depth analysis of the case study, focusing on the methods of public consultation employed in the square’s development project and evaluating their effectiveness in integrating the local community's needs. The findings demonstrate the substantial impact of residents' input on the final design, offering valuable insights into incorporating participatory practices into architectural education. The article concludes with recommendations for practitioners and educators, emphasising the importance of fostering community dialogue in design processes to address contemporary communities' diverse needs better.